2017
DOI: 10.1007/s13373-017-0104-y
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Sobolev spaces: Markov-type inequalities and duality

Abstract: Weighted Sobolev spaces play a main role in the study of Sobolev orthogonal polynomials. The aim of this paper is to prove several important properties of weighted Sobolev spaces: separability, reflexivity, uniform convexity, duality and Markov-type inequalities.Communicated by Ari Laptev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…First, we replace the function c 1 (α, β)(n + 1) max{α,β}+1 by a smallest one, and we remove the hypothesis max{α, β} ≥ −1/2. As a consequence of Theorem 1.1, we improve some Markov-type inequalities in weighted Sobolev spaces which appear in [21].…”
Section: Lupaş-type Inequality and Applications To Markov-type Inequamentioning
confidence: 92%
See 2 more Smart Citations
“…First, we replace the function c 1 (α, β)(n + 1) max{α,β}+1 by a smallest one, and we remove the hypothesis max{α, β} ≥ −1/2. As a consequence of Theorem 1.1, we improve some Markov-type inequalities in weighted Sobolev spaces which appear in [21].…”
Section: Lupaş-type Inequality and Applications To Markov-type Inequamentioning
confidence: 92%
“…for every n ∈ N and P ∈ P n , where q = max{α, β} ≥ −1/2 and q = min{α, β}. By using Lupaş' inequality and the asymptotic behavior of Gamma function, the authors showed in [21] that there exists a constant c 1 (α, β), which just depends on α and β, such that…”
Section: Lupaş-type Inequality and Applications To Markov-type Inequamentioning
confidence: 99%
See 1 more Smart Citation
“…Uniformly convex spaces are reflexive and their dual spaces are uniformly convex, too. Examples of uniformly convex spaces are L p and ℓ p , p ∈ (1, ∞) as well as Sobolev spaces W m p , p ∈ (1, ∞) [36] and Orlicz spaces [30]. Therefore L 1 , L ∞ and C[0, 1] are not uniformly convex.…”
Section: R-uniformly Convex Spacesmentioning
confidence: 99%
“…In [8], the authors considered the Fourier series for polynomials associated to the Sobolev-type inner product (7) f, g S =…”
Section: Introductionmentioning
confidence: 99%